Automatic method for searching impossible differentials and zero-correlation linear hulls of ARX block ciphers - Ya HAN (网络与信息安全学报, 2017)
Firstly,the differences and linear masks propagation equations of ARX ciphers were established.Secondly,the propagation equations were solved by SAT solver and judged valid or not.Finally,differences and linear masks were traversed to search impossible differentials and zero-correlation linear hulls automatically.The proposed algorithm was applied to TEA,XTEA and SIMON family block ciphers.The optimal impossible differentials and zero-correlation linear hulls for TEA,XTEA and SIMON family block ciphers were proposed.Moreover，with DDT and LAT,the algorithm can also be applied to search the impossible differentials and zero-correlation linear hulls of S-box based block ciphers.